2014
DOI: 10.1016/j.ccl.2014.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Atrial Fibrillation

Abstract: Summary Atrial fibrillation (AF) is the most common sustained cardiac arrhythmia in humans. However its mechanisms are poorly understood and AF therapy is often sub-optimal. This article reviews recent experimental, numerical and clinical data on dynamics of wave propagation during AF and its mechanistic link to ionic and structural properties of the atria. At the outset, we review numerical and optical mapping data suggesting that the sustained activity of periodic drivers (rotors) with exceedingly high domin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 48 publications
1
8
0
1
Order By: Relevance
“…The in-silico observation in this study that ablation based on DF terminated AF suggests that mother rotors are very likely a mechanism of AF maintenance considering that the area of highest DF coincides with the mother rotor area. This antiarrhythmic effect of DF-based ablation is consistent with the results of several studies reported in the literature [ 11 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The in-silico observation in this study that ablation based on DF terminated AF suggests that mother rotors are very likely a mechanism of AF maintenance considering that the area of highest DF coincides with the mother rotor area. This antiarrhythmic effect of DF-based ablation is consistent with the results of several studies reported in the literature [ 11 ].…”
Section: Discussionsupporting
confidence: 92%
“…Mother rotors have been considered a mechanism of AF initiation and maintenance for the past few decades, though the concept was initially proposed a century ago [ 8 11 ]. Much experimental evidence and in silico validations have supported the role of mother rotors in AF [ 8 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well-established that the onset of an AF episode triggers subsequent and more severe AF episodes, leading to electrical and structural remodeling of the diseased heart, a condition quoted as “AF begets AF” [ 17 ]. Electrical remodeling involves progressive changes in the cardiac electrical properties, leading to early afterdepolarization, delayed afterdepolizations and/or changes in the action potential duration configuration [ 17 ], culminating thus in rotor formation [ 18 ]. In this context, a pivotal role of reactive oxidative stress has been recently reported [ 19 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a stable mother rotor is known to induce fibrillatory conduction, and thereby is a key for sustaining AF [5, 7, 27]. Haissaguerre et al [28] suggested that organized and discrete sources of AF exist in human AF patients, and showed that a local radiofrequency ablation could terminate AF.…”
Section: Discussionmentioning
confidence: 99%